Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Low temperature route to prepare LaMnO3 - Daundkar, A.; Kale, Sangeeta N.; Gokhale, Suresh P.; Ravi, V (Materials Letters, 2006)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare LaMnO3(LM) ceramics. Freshly co-precipitated lanthanum and manganese hydroxides gel is allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 300 degrees C to form crystalline LM powders. This is the lowest temperature so far reported for the formation of LaMnO3. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Chemical synthesis; LaMnO3; Precipitation; transmission electron microscopy; X-ray diffraction

Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

Anomalous microwave heating effects in Ce-doped La(0.7)Sr(0.3)MnO(3): possible role of grain boundary capacitative effects across cerium solubility limit - Kale, Sangeeta N.; Mona, J.; Lofland, S. E.; Kulkarni, S. D.; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
Ce-doped manganite bulk nanocompacts [La(0.7-x)Ce(x)Sr(0.3)MnO(3) (0 < x < 0.1)] are studied for their microwave heating properties at 2.45 GHz. The heating effect is found to be nonmonotonic as a function of cerium concentration, and anomalously large heating (burning) is observed for a small concentration window near x=0.03. The x-ray diffraction studies show signatures of CeO(2) phase in x>0.03 samples. The various characterizations collectively point to the key role of the developing grain boundary CeO(2) layer which leads to highest capacitative intergrain-coupling and related charging-discharging effects when it is thinnest near the apparent Ce solubility limit of x similar to 0.03. (c) 2008 American Institute of Physics.

La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides

Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Zinc oxide nanoparticles as novel alpha-amylase inhibitors - Dhobale, Sandip; Thite, Trupti; Laware, S. L.; Rode, C. V.; Koppikar, Soumya J.; Ghanekar, Ruchika-Kaul; Kale, Sangeeta N. (Journal of Applied Physics, 2008)
Amylase inhibitors, also known as starch blockers, contain substances that prevent dietary starches from being absorbed by the body via inhibiting breakdown of complex sugars to simpler ones. In this sense, these materials are projected as having potential applications in diabetes control. In this context, we report on zinc oxide nanoparticles as possible alpha-amylase inhibitors. Zinc oxide nanoparticles have been synthesized using soft-chemistry approach and 1-thioglycerol was used as a surfactant to yield polycrystalline nanoparticles of size similar to 18 nm, stabilized in wurtzite structure. Conjugation study and structural characterization have been done using x-ray diffraction technique, Fourier transform infrared spectroscopy, UV-visible spectroscopy, and transmission electron microscopy. Cytotoxicity studies on human fibrosarcoma (HT-1080) and skin carcinoma (A-431) cell lines as well as mouse primary fibroblast cells demonstrate that up to a dose of 20 mu g/ml, ZnO nanoparticles are nontoxic to the cells. We report for the first time the alpha-amylase inhibitory activity of ZnO nanoparticles wherein an optimum dose of 20 mu g/ml was sufficient to exhibit 49% glucose inhibition at neutral pH and 35 degrees C temperature. This inhibitory activity was similar to that obtained with acarbose (a standard alpha-amylase inhibitor), thereby projecting ZnO nanoparticles as novel alpha-amylase inhibitors. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.3009317]

Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline

Characterization of biocompatible NiCo2O4 nanoparticles for applications in hyperthermia and drug delivery - Kale, Sangeeta N.; Jadhav, Anil D.; Verma, Seema; Koppikar, Soumya J.; Kaul-Ghanekar, Ruchika; Dhole, Sanjay D.; Ogale, Satishchandra B. (Nanomedicine-Nanotechnology Biology and Medicine, 2012)
Monodispersed, superparamagnetic nickel cobaltite (NCO) nanoparticles were functionalized using mercaptopropionic acid (MPA). MPA conjugates with NCO forming a metal-carboxylate linkage, with the MPA-MPA interaction occurring via formation of disulfide bonds, leaving another carboxyl end free for additional conjugation. The cytotoxicity studies on NCO-MPA show cell viability of similar to 100% up to a dosage of 40 mu g/mL on SiHa, MCF7, and B16F10 cell lines, and on mouse primary fibroblasts. Time-dependent cell viability studies done for a duration of 72 hours showed the cell lines' viability up to 80% for dosages as high as 80 mu g/mL. Negligible leaching (<5 ppm) of ionic Co or Ni was noted into the delivery medium. Upon subjecting the NCO-MPA dispersion (0.1 mg/mL) to radiofrequency absorption, the nanoparticles were heated to 75 degrees C within 2 minutes, suggesting its promise as a magnetic hyperthermia agent. Furthermore, the amino acid lysine and the drug cephalexin were successfully adducted to the NCO system, suggesting its potential for drug delivery. From the Clinical Editor: NCO-MPA nanopartciles were found to be promising magnetic hyperthermia agents, suggesting potential future clinical applications. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cytotoxicity; drug delivery; Magnetic hyperthermia; Magnetic nanoparticles

Controlled release of antimicrobial Cephalexin drug from silica microparticles - Rao, B. V. Bhaskara; Mukherji, Ruchira; Shitre, G.; Alam, F.; Prabhune, Asmita; Kale, Sangeeta N. (Materials Science & Engineering C-Materials for Biological Applications, 2014)
Release of antimicrobial drugs in a controlled fashion for extended duration of time has been investigated for long. Such controlled-drug-releasing materials show promising applications in medicinal bandages. Along with antimicrobial agents, one could also incorporate other therapeutic drugs, to make such bandages more versatile. In this context, silica micro particles were synthesized using direct reduction method, in which the synthesis was done in the presence of Cephalexin. Cephalexin was chosen as an antimicrobial candidate. The morphological characterization shows formation of monodispersed, silica microparticles of similar to 200 nm in size. The FTIR spectroscopy shows weak interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. Upon conjugation, the UV-vis spectroscopy shows persistence of the Cephalexin signature, especially its R group, confirming its antimicrobial activity even after conjugation. Loading studies reveal 12% Cephalexin loading on silica. The antimicrobial studies were done on three micro-organisms, namely, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Using zone-of-inhibition studies, it was found that E. coli, did not respond to the delivery of Cephalexin either directly or via microparticles. However, for both S. aureus and B. subtilis, the particles showed controlled release of Cephalexin for the duration of 48 h and continued maintenance and even increase in the zone of inhibition. This work demonstrates an effective protocol to prepare antimicrobial patches for controlled drug delivery. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial; Medicinal bandage; Silica microparticles; sustained drug release